Perceptions of Cannabis Use and Its Benefits and Risks Among Breastfeeding Mothers - Zane Boerner; Cristina Natha; Teresa Baker; Christine D. Garner (Women's Health Reports)
Background: Approximately 5% of breastfeeding women report using cannabis. Little is understood about perceived benefits and risks of cannabis use; thus, this study aimed to fill this gap. Methods: An anonymous online survey was conducted from 2018 to 2019 among breastfeeding women (n = 1516) who used cannabis. Data collected included demographics, frequency and timing of cannabis use, perceived effects in infants, and repercussions experienced. Analyses included descriptive statistics; chi-square and t-tests were used to test differences between groups (SPSSv28). A subset (n = 413) left open-text responses about cannabis and its perceived risks and benefits. Content analysis and ATLAS.ti were used for open-ended responses. Results: Two-thirds (67%) of participants were “not at all” concerned that cannabis use while breastfeeding affected their baby. Only 3% attributed symptoms in their infants to cannabis use; symptoms were perceived as positive or negative. Interestingly, 45% (n = 603) altered timing of cannabis use relative to breastfeeding to avoid exposing their infant to cannabis. Most mothers (85.8%) reported no changes in their breast milk supply. Few respondents were investigated by Child Protective Services (6.9%) or arrested (3.8%) for cannabis use. In open-ended responses, three themes emerged about the perceptions of cannabis use while breastfeeding: (1) cannabis preferred to address medical concerns, (2) positive impact of cannabis on quality of life for mothers and their children, and (3) concerns about negative consequences. Conclusion: Breastfeeding mothers who used cannabis reported positive perceptions of cannabis as a safer alternative to medications, yet concerns existed about legal repercussions. Understanding maternal perceptions may be useful in developing successful approaches to counseling mothers about cannabis use.